+0  
 
0
30
1
avatar+21 

Solve for z in the literal equation

2/3(z + 5) = y.

 
KaylaDoodlez  Oct 11, 2017
social bar

Best Answer 

 #1
avatar+4697 
+2

\(\frac23\)(z + 5)  =  y

                                                Multiply both sides of the equation by  \(\frac32\)

 \(\frac32\) *  \(\frac23\)(z+5)  =   \(\frac32\)y

 

z + 5  =  \(\frac32\)y

                                                Subtract  5  from both sides of the equation.

z  =  \(\frac32\)y - 5

 
hectictar  Oct 11, 2017
Sort: 

1+0 Answers

 #1
avatar+4697 
+2
Best Answer

\(\frac23\)(z + 5)  =  y

                                                Multiply both sides of the equation by  \(\frac32\)

 \(\frac32\) *  \(\frac23\)(z+5)  =   \(\frac32\)y

 

z + 5  =  \(\frac32\)y

                                                Subtract  5  from both sides of the equation.

z  =  \(\frac32\)y - 5

 
hectictar  Oct 11, 2017

25 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details